The Influence of Motivation, Voice Behavior and Work Engagement of the Individual Performance at Islamic Bank - Ely Kartikaningdyah; Randa Okta Surya (Journal of Applied Accounting and Taxation, 2017)
This study discusses the problems frequently experienced by human resource managers in improving the performance of individual employees at Islamic banks. In this regard has been expressed by the fact that the need for human resources (HR) at Islamic banks much needed especially qualified individual performance. This study purpose to prove that the behavior of sound, employee engagement and motivation have an influence on the performance of the individual in Islamic banks. The method used is quantitative approach with a simple linear regression analysis to prove the independent variable (sound behavior, work engagement and motivation) have an influence on the dependent variable (performance of individuals). The sample used in this study is limited to the existing Islamic banks. The results of this study can be used as a reference for HR managers at companies, especially in the banking sector. For further research is expected to add to the object and the amount of sample, is not limited to only Islamic banks but coupled with commercial banks (conventional).